2009
DOI: 10.3109/09513590903159664
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis in Italy: From cost estimates to new medical treatment

Abstract: Endometriosis is defined as the presence of endometrial-like tissue outside the uterus, which induced a chronic inflammatory reaction. The data collected from Italy showed that around 3 million women are affected by endoemtriosis and the condition was predominantly found in women of reproductive age (50% of women were in the 29-39 age range), only 25% of women were asymptomatic. The associated symptoms can create an impact in general physical, mental, and social well-being. Endometriosis is associated with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…49 The identification of precise molecular targets is therefore a necessary step. Angiogenesis is a key event in the maintenance of endometrial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…49 The identification of precise molecular targets is therefore a necessary step. Angiogenesis is a key event in the maintenance of endometrial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that the disease is present in around 1.5% of the general female population and 6-15% of hospitalized women [4]. The data provided by the Italian Agency for Medicinal Products report that in Italy the prevalence of endometriosis in asymptomatic women varies from 2% to 22%, depending on the diagnostic criteria used and the population studied: in women with severe dysmenorrhea and chronic pelvic pain the percentage ranges from 40 to 60% and in women with subfertility it sets around 20% and 30% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis is a common condition, affecting a rather large fraction of menstruating women, characterized by the hormone-dependent persistence and growth of vascularized endometrial tissue at ectopic sites, typically the pelvis, with pain and reduced fertility (Lebovic et al, 2001; Giudice and Kao, 2004; Berkley et al, 2005; Bulun, 2009; Luisi et al, 2009; Giudice, 2010; Simoens et al, 2012). Lesions are thought to originate from endometrial fragments shed during menstruations, which reach via the Fallopian tubes the peritoneal cavity.…”
Section: Introductionmentioning
confidence: 99%